Experiences of rehabilitation one year after breast cancer diagnosis–A focus group study from the ReScreen randomized controlled trial - Ing-Marie Olsson; Charlotta Dykes; Lisa Rydén; Ulrika Olsson-Möller; Marlene Malmström (PLoS ONE, 2025)
Background Treatment for breast cancer poses major challenges and leads to a variety of side-effects and problems that affect life for a long time. Experiences and symptoms vary, and research indicates a lack of structures for ensuring individualized rehabilitation. This qualitative focus group study aims to explore the experience of women with BC after participating in a complex randomized controlled trial (RCT) (Clinicaltrials.gov NCT03434717) focusing on cancer rehabilitation from a comprehensive perspective. Method Nine semi-structured focus group interviews with women (n = 30) who participated in the Rescreen RCT were conducted. The women were interviewed divided into three RCT groups (intervention, control, or observation group). Data were initially analyzed inductively using conventional content analysis, followed by a deductive approach, guided by the result from the inductive analysis. Results The inductive analysis resulted in two categories and four sub-categories and showed a great variation in experiences and needs. Some women described a well-functioning process, while others described lack of individualized information, continuity with healthcare providers, and clear pathways for support. After the deductive analysis, a variation between the groups appeared. Women in the intervention group expressed that a proactive and individualized approach facilitated rehabilitation and they experienced a feeling of being recognized as a person, which they highlighted as important. On the contrary, women from the control group described feelings of being abandoned from healthcare, hindering rehabilitation. The observation group expressed that their needs had been fulfilled within the healthcare system. Conclusions This study adds important knowledge to the evaluation of the ReScreen model and contributes to existing research on how individualized rehabilitation after breast cancer can be applied in clinical practice. A proactive, person-centered approach in rehabilitation, aimed at those with extended needs, would potentially optimize rehabilitation and facilitate the recovery process after breast cancer treatment.